Surveillance metrics of SARS-CoV-2 transmission in central Asia: Longitudinal trend analysis - Post, Lori Ann; Benishay, Elana T.; Moss, Charles B.; Murphy, Robert L.; Achenbach, Chad J.; Resnick, Danielle (JMIR Publications, 2021)
SARS-CoV-2, the virus that caused the COVID-19 global pandemic, has severely impacted Central Asia, resulting in a high caseload and deaths that varied by country in Spring 2020. The varying severity of the pandemic is explained by differences in prevention efforts in the form of public health policy, adherence to those guidelines, as well as socio-cultural, climate, and population characteristics. The second wave of the COVID-19 currently is breaching the borders of Europe. Public health surveillance is necessary to inform and guide leaders; however, existing surveillance explains past transmissions obscuring shifts in the pandemic, increases in infection rates, and the persistence in the transmission of COVID-19.